The Aryl Hydrocarbon Receptor (AhR) in the Aging Process: Another Puzzling Role for This Highly Conserved Transcription Factor - Brinkmann, Vanessa; Ale-Agha, Niloofar; Haendeler, Judith; Ventura, Natascia (Frontiers in Physiology, 2020)
Aging is the most important risk factor for the development of major life-threatening diseases such as cardiovascular disorders, cancer, and neurodegenerative disorders. The aging process is characterized by the accumulation of damage to intracellular macromolecules and it is concurrently shaped by genetic, environmental and nutritional factors. These factors influence the functionality of mitochondria, which play a central role in the aging process. Mitochondrial dysfunction is one of the hallmarks of aging and is associated with increased fluxes of ROS leading to damage of mitochondrial components, impaired metabolism of fatty acids, dysregulated glucose metabolism, and damage of adjacent organelles. Interestingly, many of the environmental (e.g. pollutants and other toxicants) and nutritional (e.g. flavonoids, carotenoids) factors influencing aging and mitochondrial function also directly or indirectly affect the activity of a highly conserved transcription factor, the Aryl hydrocarbon Receptor (AhR). Therefore, it is not surprising that many studies have already indicated a role of this versatile transcription factor in the aging process. We also recently found that the AhR promotes aging phenotypes across species. In this manuscript, we systematically review the existing literature on the contradictory studies indicating either pro- or anti-aging effects of the AhR and try to reconcile the seemingly conflicting data considering a possible dependency on the animal model, tissue, as well as level of AhR expression and activation. Moreover, given the crucial role of mitochondria in the aging process, we summarize the growing body of evidence pointing towards the influence of AhR on mitochondria, which can be of potential relevance for aging.